Efeito imunomodulatório das lectinas de Synadenium carinatum (ScLL) e Artocarpus heterophylus (Artin M) no controle da toxoplasmose - Souza, Leandro Peixoto Ferreira de (2015)
ScLL and Artin M are lectins from the Synadenium carinatum latex and Artocarpus heterophyllus seeds that have important role in modulation of immune responses to pathogens. Considering that there are no reports in the literature focusing in the role of these lectins for toxoplasmosis treatment and that this protozoan disease is a serious health public problem caused by Toxoplasma gondii, the aim of this study was to evaluate the immunomodulatory effect of ScLL and Artin M in treatment of toxoplasmosis. First, we performed a cytotoxicity assays in bone marrow-derived macrophages (BMDMs) from C57BL/6 mice with different lectin concentrations. After, we investigated the in vitro cytokine and nitric oxide (NO) production by macrophages derived from BMDM cells, when stimulated with different lectin concentrations. We found that amounts higher than 1.8 μg of ScLL were cytotoxic for host cells, whereas Artin M had no cytotoxic effect. Also, ScLL presented high capacity to induce pro-inflammatory cytokine in macrophages, such IL-12, while Artin M had high potential to induce both pro and anti-inflammatory profile, by IL-10 and IL-12 production. Further, both lectins were able to increase macrophages NO levels. Hence, we evaluated the treatment effect of ScLL and Artin M in C57BL/6 mice infected by ME-49 strain of T. gondii. The animals were infected and treated with ScLL, Artin M, Artin M plus ScLL or sulfadiazine, and analyzed for cytokine production, brain parasite burden and mortality. Our results demonstrated that ScLL and Artin M were able to increase cytokines levels also in in vivo model, presenting stronger immunostimulatory effect. In addition, parasite burden was lower on mice treated with ScLL or Artin M plus ScLL. Also we found a higher survival rate in animals treated with ScLL compared to untreated. Overall, our findings suggests that the immunomodulatory mechanisms mediated by lectins ScLL and Artin M can contribute to the control of T. gondii infection.